WHISKIT.CO Mobile Ordering Application - KUNSURAMAN, SUTAHTH; Mohd Hamdi Irwan Hamzah (Applied Information Technology And Computer Science, 2025)
Whiskit.co, a made-to-order tart and cupcake shop in Gombak, ensures product freshness by preparing items upon order. However, the business faces significant challenges with long customer wait times and inaccurate tracking due to manual processes and more. To address these issues, a mobile ordering application is developed using the Prototyping methodology. This iterative approach enabled continuous user feedback and refinement. There are eigth modules that will be discussed in this proposed project, which is login and signup, manage profile, manage product, manage staff, manage order, make a payment, generate report and manage feeback. This proposed project developed using a object-oriented approach. The application was iteratively developed with React Native for cross-platform compatibility and Firebase for real-time operations, the app streamlines ordering and facilitates real-time communication. Hopefully, this application will help Whiskit.co shop reduce these problem.